2021
DOI: 10.1371/journal.pone.0254807
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of economic burden with biologic treatments in Crohn’s disease patients: A mirror image study using an insurance database in Japan

Abstract: Biologics are recommended in Japan to treat moderate to severe Crohn’s Disease (CD). Although CD is associated with high direct costs in Japan, updated information after ustekinumab’s approval is unavailable. We aimed to evaluate the healthcare resource utilization (HRU) and associated direct costs from the payer’s perspective in Japan. Claims data (2010–2018) were retrospectively analyzed to identify patients with CD. HRU and associated costs were evaluated for 12 months before and after biologic initiation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…The proportion of adult patients with IBD under treatment with anti-tumor necrosis factor (anti-TNF) in Asia differs markedly, from as high as 40% in Japan (in 2021) to as low as 10% in Malaysia (in 2019). 81,82 A study on pediatric IBD from India reported that biologics were used in 18% of children with an onset <16 years. 83 Data on the use of other biologics such as golimumab, 84 ustekinumab, 85,86 vedolizumab, 87 and tofacitinib in childhood IBD in Asia are lacking.…”
Section: Biologicsmentioning
confidence: 99%
“…The proportion of adult patients with IBD under treatment with anti-tumor necrosis factor (anti-TNF) in Asia differs markedly, from as high as 40% in Japan (in 2021) to as low as 10% in Malaysia (in 2019). 81,82 A study on pediatric IBD from India reported that biologics were used in 18% of children with an onset <16 years. 83 Data on the use of other biologics such as golimumab, 84 ustekinumab, 85,86 vedolizumab, 87 and tofacitinib in childhood IBD in Asia are lacking.…”
Section: Biologicsmentioning
confidence: 99%
“…In Japan, biologics are recommended to treat moderate-to-severe CD. A mirror image study using an insurance database showed that 51% of patients with CD are on biologics [ 3 ].…”
mentioning
confidence: 99%